Clinical outcome analysis of surgical treatment for primary retroperitoneal leiomyosarcoma - Li Yang; Qiu Hui; Wu Jianhui; Li Chengpeng; Liu Bonan; Liu Qiao; Hao Chunyi; Lv Ang (结直肠肛门外科, 2022)
[Objective] To analyze the clinical outcomes of surgical treatment for primary retroperitoneal leiomyosarcoma (RLMS). [Methods] Clinical data of 41 RLMS patients treated at the Soft Tissue and Retroperitoneal Tumor Center of Peking University Cancer Hospital from 2011 to 2020 were retrospectively analyzed. Surgical-related indicators, postoperative complications (graded according to the Clavien-Dindo classification), perioperative mortality, and postoperative follow-up were evaluated. [Results] Among the 41 patients, 28 (68.3%) had single tumors and 13 (31.7%) had multiple tumors. FNCLCC grading: G1 in 2 cases (4.9%), G2 in 24 cases (58.5%), and G3 in 15 cases (36.6%). Complete resection was achieved in 40 patients (97.6%), while 1 patient could not achieve complete resection due to multiple fused abdominal and pelvic tumors. Combined organ resection was performed in 38 patients (92.7%), with a total of 155 organs resected. The main resected organs included the colon and rectum, ureter, major blood vessels, kidney, small intestine, uterus, spleen, gallbladder, and the body and tail of the pancreas. Three cases involved only the resection of retroperitoneal tumors. Among the patients, 26 (63.4%) did not undergo major blood vessel resection, while 15 (36.6%) underwent combined major blood vessel resection, including the inferior vena cava (6 cases), iliac artery and vein (4 cases), iliac vein (2 cases), inferior vena cava and iliac artery (1 case), inferior vena cava and iliac vein (1 case), and superior mesenteric vein (1 case). Artificial blood vessels were used for reconstruction in 9 cases due to large vascular defects (4 inferior vena cava, 5 iliac vessels). The median maximum diameter of the resected tumors was 10 (7, 19) cm, the median operation time was 5.7 (3.9, 7.1) hours, the median intraoperative blood loss was 400 (200, 1,500) mL, and the median postoperative hospital stay was 14 (10, 20) days. Postoperative complications occurred in 7 patients (17.1%), including Grade I in 1 case (2.4%) with artificial vascular replacement, Grade II in 4 cases (9.8%) with 1 case of artificial vascular replacement, and Grade IV in 2 cases (4.9%) with 1 case of artificial vascular replacement. There were no perioperative deaths. Postoperative follow-up lasted for a median of 50.0 (32.6, 71.5) months, with no patients lost to follow-up. During the follow-up period, 13 patients experienced local recurrence, 11 had distant metastases (4 cases of lung metastases, 3 cases of liver metastases, 3 cases of both liver and lung metastases, and 1 case of limb metastasis), and 10 patients died. The median overall survival of the patients was not reached, with a 5-year overall survival rate of 65.7% and a disease-free survival rate of 54.5%. [Conclusion] En bloc resection with combined organ resection, including combined major blood vessel resection, is generally safe and feasible, showing satisfactory therapeutic effects for RLMS.